2012
DOI: 10.1083/jcb.201205115
|View full text |Cite
|
Sign up to set email alerts
|

Bub1 kinase activity drives error correction and mitotic checkpoint control but not tumor suppression

Abstract: Mice expressing a version of Bub1 that lacks kinase activity have increased chromosome segregation errors and aneuploidy but not increased susceptibility to tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
128
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(143 citation statements)
references
References 77 publications
14
128
1
Order By: Relevance
“…S1A), but there was a 40% decrease in the amount of Aurora B kinase localized to centromeres. Instead, Aurora B kinase localized along the length of chromosome arms, similar to the localization observed when Bub1, Sgo1 or Wapl are disrupted (Ricke et al, 2012;Rivera et al, 2012;Haarhuis et al, 2013). This change in localization of Aurora B kinase was mimicked by the distribution of INCENP (Fig.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…S1A), but there was a 40% decrease in the amount of Aurora B kinase localized to centromeres. Instead, Aurora B kinase localized along the length of chromosome arms, similar to the localization observed when Bub1, Sgo1 or Wapl are disrupted (Ricke et al, 2012;Rivera et al, 2012;Haarhuis et al, 2013). This change in localization of Aurora B kinase was mimicked by the distribution of INCENP (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Recently, it was demonstrated that Bub1 is required for efficient centromere localization of the CPC (Ricke et al, 2012). One function of Bub1 is to localize the CPC to the centromere by phosphorylating threonine 120 on histone H2A (phospho-H2A T120) (Kawashima et al, 2010;Watanabe, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Since the discovery of BUB1, the molecular mechanism by which it participates in SAC activation has been a matter of controversy. Studies in mice, budding yeast and fission yeast have shown that BUB1 kinase activity is required for SAC activation (Kawashima et al, 2010;Ricke et al, 2012;Yamaguchi et al, 2003), but this has been contradicted by other studies using the same model organisms (Baker et al, 2009;Fernius and Hardwick, 2007;London and Biggins, 2014;Perera et al, 2007;Rischitor et al, 2007;Warren et al, 2002). Human cell studies have proven equally inconsistentone study proposes that BUB1 directly phosphorylates and inhibits CDC20 (Kang et al, 2008), whereas another shows that a truncated BUB1 protein lacking the kinase domain significantly restored SAC activity to BUB1-depleted cells (Klebig et al, 2009).…”
Section: Introductionmentioning
confidence: 70%
“…In addition, neither the presence of KI1 nor KI2 in Knl1 is an absolute requirement for SAC activity or chromosome alignment (Krenn et al, 2012;Yamagishi et al, 2012). Moreover, although the Bub1 TPR domain has been reported to be necessary for optimal Bub1 kinase activity (Krenn et al, 2012;Ricke et al, 2012), a Bub1 TPR mutant that is unable to interact with KI1 does not exhibit altered kinase activity or kinetochore localization of Bub1 (Krenn et al, 2012;Yamagishi et al, 2012), suggesting that it is not the interaction with KI1 per se that promotes catalytic activity. Similarly, KI2 is not necessary for the robust kinetochore recruitment of BubR1 (Yamagishi et al, 2012).…”
Section: Wd40 Repeatmentioning
confidence: 99%